Clinical Efficacy of a Spray Containing Hyaluronic Acid and Dexpanthenol after Surgery in the Nasal Cavity (Septoplasty, Simple Ethmoid Sinus Surgery, and Turbinate Surgery). (1st July 2014) - Gouteva, Ina; Shah-Hosseini, Kija; Meiser, Peter
Abstract : Background . This prospective, controlled, parallel-group observational study investigated the efficacy of a spray containing hyaluronic acid and dexpanthenol to optimise regular treatment after nasal cavity surgery in 49 patients with chronic rhinosinusitis. Methods . The control group received standard therapy. Mucosal regeneration was determined using rhinoscopy sum score (RSS). Pre- and postoperative nasal patency was tested using anterior rhinomanometry. The participants were questioned about their symptoms. Results . Regarding all RSS parameters (dryness, dried nasal mucus, fibrin deposition, and obstruction), mucosal regeneration achieved good final results in both groups, tending to a better improvement through the spray application, without statistically significant differences during the whole assessment period, the mean values being 7.04, 5.00, 3.66, and 3.00 (intervention group) and 7.09, 5.14, 4.36, and 3.33 (control group). No statistically significant benefit was identified for nasal breathing, foreign body sensation, and average rhinomanometric volume flow, which improved by 12.31% (control group) and 11.24% (nasal spray group). Conclusion . The investigational product may have additional benefit on postoperative mucosal regeneration compared to standard cleaning procedures alone. However, no statistically significant advantage could be observed in this observational study. Double-blind, controlled studies with larger populations will be necessary to evaluate the efficacy of this treatment modality.